EVALUASI KUALITAS WEBSITE E-COMMERCE ZI-SHOP DENGAN MODEL SQO-OSS MENGGUNAKAN METODE PROFILE MATCHING - Mohammad Ferdian Saputro; Harsya Mahardika Pratama; Adhek Satrya Alfiansyah; Muhammad Naufal Dzaky Robbaniyyin; Rani Purbaningtyas (LPPM Universitas Dhyana Pura, 2026)
The development of digital technology has encouraged businesses to shift from conventional methods to digital platforms, such as e-commerce. However, challenges such as high commission fees in the marketplace encourage MSMEs to develop independent e-commerce websites. This study aims to evaluate the software quality of ZI-Shop, an independent e-commerce website developed using Laravel and Livewire at Politeknik Negeri Jember. The evaluation was conducted based on three software quality indicators according to the SQO-OSS model, namely maintainability, reliability, and security. The research used the profile matching method to compare the actual profile of application quality with a predetermined ideal profile. The data was collected through a questionnaire using a 1-5 Likert scale distributed to 20 respondents who use the ZI-Shop application. The weight of maintainability and reliability indicators was 40%, and security was 20%, while core factors and secondary factors were given a weight of 60% and 40% respectively. The final results of the profile matching method are used to calculate the level of conformity of application quality to the expected ideal value. This research is expected to provide an objective picture of the quality of the ZI-Shop application and become a reference in the development of other independent e-commerce websites in order to increase the efficiency and profitability of online businesses.